2011
DOI: 10.1063/1.3610510
|View full text |Cite
|
Sign up to set email alerts
|

Two-color interferometry and shadowgraphy characterization of an orthogonal double-pulse laser ablation

Abstract: Orthogonal double pulse laser ablation on aluminum target at atmospheric pressure was studied by time-resolved optical emission spectroscopy, shadowgraphy and two-color interferometry. Studies were realized as a function of the distance from the first pulse plasma induced in air to the sample surface. The evolution of the electron and neutral particles densities were determined by two-color interferometry. Line intensification mechanisms are discussed based on the interferometry results and the plumes interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Thus, the vaporized material will expand to a larger volume at a faster rate than in normal atmospheric conditions, i.e. SP-LIBS [16,41,42]. As a result, the particle number density is reduced, which is translated in a slower recombination rate.…”
Section: Pre-ablation Schemementioning
confidence: 96%
See 3 more Smart Citations
“…Thus, the vaporized material will expand to a larger volume at a faster rate than in normal atmospheric conditions, i.e. SP-LIBS [16,41,42]. As a result, the particle number density is reduced, which is translated in a slower recombination rate.…”
Section: Pre-ablation Schemementioning
confidence: 96%
“…In a previous work [41], we observed that the temperature near the sample surface in the pre-ablative configuration exceeds the Al target fusion value for up to 40 μs. Then, thermal energy is transferred to the sample facilitating the ablation process due to a reduction of the deposited energy required to vaporize the sample.…”
Section: Pre-ablation Schemementioning
confidence: 96%
See 2 more Smart Citations
“…The analytical performance of the DP-LIBS technique is strongly dependent on the selection of the experimental conditions. Several research groups focused on optimizing the experimental parameters by DP laser systems [22][23][24] to improve the sensitivity of LIBS. The enhancement in emission line intensity using collinear DP excitation is due to an increase in ablation efficiency, longer plasma life time and higher plasma temperature.…”
Section: Introductionmentioning
confidence: 99%